БЛАЗОНИРАЊЕ НА СТЕМАТОГРАФИИТЕ НА ВИТЕЗОВИЌ И ЖЕФАРОВИЌ - BLAZONING THE STEMMATOGRAPHIAS OF VITEZOVIC AND ZHEFAROVIC - Jovan Jonovski (Македонски хералд - Macedonian Herald, 2020)
Vitezovic’s Stemmatographia (1701)  and Zhefarovic’s translation into Slavic (1741), along with the Illyrian roll of arms (Korenic-Neoric, London, Fojnica, and other transcriptions) are part of the so-called Illyrian Heraldry, the central heraldic source for the Slavic Balkans of the 16th to 18th centuries.While the Illyrian Armorial has been blazoned in English as well as in other Slavic languages, this paper is the first attempt to blazon the 56 land coats of arms in Macedonian with standard Macedonian heraldic terminology and syntax. Also English blazon is given.An analysis of the heraldic composition and elements is also made, as well as the possible role as a blazon of the poetic verses written under each coat of arms